Clusterin in Neuroendocrine Epithelial Neoplasms: Absence of Expression in a Well-differentiated Tumor Suggests a Jejunoileal Origin. Issue 2 (February 2018) - Czeczok, Thomas W.; Stashek, Kristen M.; Maxwell, Jessica E.; O'Dorisio, Thomas M.; Howe, James R.; Hornick, Jason L.; Bellizzi, Andrew M.
Abstract : Clusterin, a widely expressed, tissue-specific glycoprotein, is a diagnostic marker of several tumor types, including anaplastic large cell lymphoma, follicular dendritic cell sarcoma, and tenosynovial giant cell tumor. A recent study has suggested it is highly expressed by well-differentiated neuroendocrine tumors (NET) arising at most anatomic sites, with the exception of jejunoileal tumors, and that it is similarly not expressed by poorly differentiated neuroendocrine carcinomas (NEC). We sought to validate this result in a large cohort of NETs and NECs. Clusterin immunohistochemistry was performed on tissue microarrays of 255 NETs [45 lung, 4 stomach, 8 duodenum, 75 pancreas (62 primary, 13 metastatic), 107 jejunoileum (69 primary, 38 metastatic), 16 appendix] and 88 NECs (43 visceral, 45 Merkel cell). Extent (%) and intensity (0, 1+, 2+, 3+) of staining were assessed and an H-score (extent x intensity) calculated. An average H-score >5 was considered positive. Clusterin expression was noted in 82.4% of 148 nonjejunoileal NETs (average H-score 183) and only 8.4% of 107 jejunoileal NETs (average H-score, 31), as well as 19.3% of NECs (average H-score, 36). Clusterin is frequently, strongly expressed by NETs of diverse anatomic sites, with the exception of jejunoileal tumors, in which it is only rarely, weakly expressed. It is occasionally, weakly expressed by NECs. Most metastatic NETs of occult origin arise in the pancreas or the jejunoileum. For cases in which an initial site of origin immunopanel (eg, islet 1, PAX6, CDX2) is ambiguous, addition of clusterin may be diagnostically useful, with absence of expression suggesting a jejunoileal origin.